A Qualitative Study to Assess the Factor affecting Decision Making Process and Experience of Water Birth Among the Women Delivered at Cherish Hospital, Surat - Shukal, Riya Patel; Mistry, Kinjal (Journal of Neonatal Surgery, 2025)
Introduction: Waterbirth is an alternative process for delivery. This process of delivery is safe and comforting. It is very effective procedure and it runs from 16th – 18th century. It started after 1970s -1980s and this attractive method started in India from 2007. Aim of the study: The aim of the study was the factors affecting decision making process and experience of waterbirth among women. Material and methods: A qualitative study with phenomenological research design was conducted on 10, women who delivered through water birth at Cherish hospital, Surat. The sample was selected through non probability sampling technique. Semi structured interview guide consists of three section such as sociodemographic data (09 items), obstetrical data (06 items) and interview questionaries. The data were collected and analyzed by using thematic analysis. Result: The result of the study derived three major themes included Perception, Motivation and experience of waterbirth among women who delivered at cherish hospital, Surat. Conclusion: It concluded that health care counselling, Family support influenced in decision making process and the positive experience of women towards water birth delivery.